KOORDINASI PENCEGAHAN TERORISME DI PROVINSI RIAU - Irawan, Dinda; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Terrorism was a serious crime that need to be discussed in Riau Province. In this case, all institution must contributed to control and prevent the causes of terrorism growing widely. Because the terrorism couldnot be managed personally, coordination between institution were important to prevent the sprouting of this serious crime. The purpose of this research was to know how well coordination between FKPT, MUI and Polda Riau in preventing the terrorism and some causes that made them incoordinate. The teory which applied this research was coordinate by Koonz, O’Donnel and Fayol. It described about teamwork; communication; distributin task; and meeting. Because this research was descriptive kualitative research, approach was useb by interviewing, observing, and documenting. The result of the research showed: first, coordination those institution in teamwork, communication and distributing task generally existed. Yet, continuously agenda of those institution to do the meeting was not often. Second, the finansial problem effected the coordination of preventing the terrorism. Keywords : Coordination, Prevention, Terrorism